The effects of lean transformation on performance measurement and capacity management : case Valmet - Heino, Henri (2016)
The study focuses on reviewing the effects of lean transformation on the case organization’s performance measurement and capacity management. The objective of the study was to identify issues in management accounting processes from the standpoint of lean production and to develop new capacity and performance measures that support lean production in the case organization.